2010
DOI: 10.1161/circulationaha.109.891077
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Potently Inhibits Hypoxic and Inflammatory Pulmonary Arterial Hypertension and Smooth Muscle Proliferation via Xanthine Oxidoreductase–Dependent Nitric Oxide Generation

Abstract: Background-Pulmonary arterial hypertension is a progressive proliferative vasculopathy of the small pulmonary arteries that is characterized by a primary failure of the endothelial nitric oxide and prostacyclin vasodilator pathways, coupled with dysregulated cellular proliferation. We have recently discovered that the endogenous anion salt nitrite is converted to nitric oxide in the setting of physiological and pathological hypoxia. Considering the fact that nitric oxide exhibits vasoprotective properties, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(189 citation statements)
references
References 52 publications
8
178
2
1
Order By: Relevance
“…has shown efficacy in reducing pulmonary pressures and preventing right ventricular hypertrophy (19)(20)(21). More recent work has demonstrated that acute IV administration of nitrite improves exercise capacity in patients with HFpEF, a group at high risk for secondary (Group 2) PH (22).…”
Section: Methodsmentioning
confidence: 99%
“…has shown efficacy in reducing pulmonary pressures and preventing right ventricular hypertrophy (19)(20)(21). More recent work has demonstrated that acute IV administration of nitrite improves exercise capacity in patients with HFpEF, a group at high risk for secondary (Group 2) PH (22).…”
Section: Methodsmentioning
confidence: 99%
“…indicates that ROS play a critical role in hypoxia-induced cell proliferation (3,9). In this study, to examine the role of ROS in the proliferation of HPASMCs, the cells were exposed to the exogenous ROS donor, H 2 O 2 .…”
Section: Ros May Not Be Involved In Chemical Hypoxia-induced Prolifermentioning
confidence: 99%
“…Reportedly, in human pulmonary artery smooth muscle cells (HPASMCs), NADPH oxidase (NOX)4 mediates cell proliferation triggered by transforming growth factor-β1 (TGF-β1) (3). The inhibition of oxidative stress with nitrite or superoxide dismutase (SOD) has been shown to ameliorate PAH (8,9). Of note, prostacyclin (also known as prostaglandin I2 or PGI 2 ), an effective but expensive clinical drug, has been used for the treatment of PAH via vasodilatation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified multiple enzymes that possess nitrite reductase activity, including XOR. This potential nitrite reductase has been suggested to be one of the predominant reductases within the vasculature (43). Based upon this knowledge, the role of XOR in mediating the effects of sodium nitrite was investigated.…”
Section: Figurementioning
confidence: 99%